The new Blackwell companion to the city - Bridge, Gary; Watson, Sophie (Wiley-Blackwell companions to geography, 2013)
"This book considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. The most interdisciplinary collection of its kind. Provides a contemporary update on urban thinking that builds on well established debates in the field Uses the city to explore economic, social, cultural, environmental and political issues more broadly. Includes contributions from non Western perspectives and cities."--